Analysis of Genetic Association of Intestinal Permeability in Healthy First-degree Relatives of Patients with Crohn's Disease. Issue 11 (28th June 2019) - Turpin, Williams; Espin-Garcia, Osvaldo; Bedrani, Larbi; Madsen, Karen; Meddings, Jonathan B; Raygoza Garay, Juan Antonio; Silverberg, Mark S; Smith, Michelle I; Griffiths, Anne M; Moayyedi, Paul; Marshall, John K; Mack, David; et al.
Abstract: Excessive intestinal permeability or intestinal barrier dysfunction as measured by various assays has been observed in various diseases. However, little is known about the factors contributing to altered gut permeability in these diseases. Our objective was to determine the genetic determinants of altered gut permeability as measured by the lactulose mannitol fractional excretion ratio (LacMan ratio) in 1075 healthy first-degree relatives of patients with Crohn's disease (CD). In a targeted analysis of single nucleotide polymorphisms (SNPs) located in genes associated with intestinal barrier function related or not to inflammatory bowel disease, we did not find a significant association with intestinal permeability. In an untargeted genome-wide association analysis, the top 100 associations were located in 22 genomic loci, although they were not statistically significant after correction for multiple testing (raw P values [1.8 × 10 –7 - 1.4 × 10 –5 ]. The lowest P value was obtained for rs9616637 (22q13.33, C22orf34 ), for which the minor allele A was associated with a decreased LacMan ratio. These results suggest that host genetic background has limited contribution toward intestinal permeability. Despite this, our study is currently the largest of its kind assessing gut permeability in vivo. It remains possible that smaller genetic effect sizes on LacMan ratio are not detectable in this sized cohort. Larger studies are warranted to identify the potential genetic contribution to intestinal permeability.